PENGARUH EKSTRAK AKAR TUBA (Derris elliptica L.) TERHADAP DAYA TETAS TELUR IKAN MAS (Cyprinus carpio L.) - Yosnita, Marfi; Ramadhan, Ramadhan; Kasmeri, S.Si, M.Si., Ria (STKIP PGRI Sumbar, 2014)
ABSTRACT In develop of the effort of carp fish culture necessary suported by preparing seeds which have good of viability. The poison roof often used by farmer for poisoning the fish to the pool. A prosess hatch egg of fish influenced many factors of areas is water quality. The aimed of this research to know influence extract poison roof to capacity hatch egg of fish it is normality larvae and abnormality larvae.The research had done at January 2014 in the Laboratory Zoology Biology Faculty of Mathematic and natural sciences University of Padang. This research is experimental research, using Complete Random Program with five treatment and six replications. This ach (P1) 0,000%, 0,002% (P2), 0,003% (P3), 0,004% (P4), and 0,005% (P5). Observation is doing to the egg thatwas hath becoming larvae after four (4) days incubation. The data about ability of hatch and abnormality larvae carp fish analyzed with ANOVA on standar significant0,05 and continue with Clarify Smaller Different. In this research be able the average produce capacity hatch of egg on act P1 92,50%, P2 80,83%, P3 77,50%, P4 74,17% and P5 72,50%. Percentatiton ability of higher hatch in P1 diferent (p< 0,05) considered act P2, P3, P4 and P5. Average of larvae is normality in act P1 99,12%, P2 98,49, P3 97,92, P4 96,22% and P5 95,30%, average abnormality larvae is P1 0,88%, P2 1,51%, P3 2,08%, P4 3,78% and P5 4, 71%. The presentation of normality larvae and abnormality larvae not have influence. Itcan be concinded that decreased of viability of carp egg and not has influence to the presentation normality and abnormality larvae in carp fish.